IMPLEMENTATION OF SISKEUDES IN TAMBAK KALISOGO VILLAGE, JABON DISTRICT, SIDOARJO REGENCY - Maylita, Betari Rus; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine how the Village Financial System (SISKEUDES) is implemented in Tambak Kalisogo Village, Jabon District, Sidoarjo Regency. Method: The method used in this study is a descriptive qualitative approach, where data collection is conducted through interviews, observation, and documentation, supplemented by secondary data from academic articles and official documents. The analysis in this study refers to Edward III's implementation theory, consisting of four indicators: communication, resources, implementer attitudes, and bureaucratic structure. Results: The results show that the implementation of SISKEUDES in the village has been carried out, although it still faces various obstacles. Some of the problems encountered include a lack of skilled implementers, inadequate technological infrastructure, and technical problems such as unstable internet connections. Nevertheless, communication between village officials and related agencies is quite effective, and the bureaucratic structure supports program implementation well. Novelty: To improve the implementation of SISKEUDES, regular training for village officials and improvements to supporting infrastructure are needed. Support from the local government and community participation are also key factors in realizing transparent and accountable village financial management.